2000
DOI: 10.1097/00007632-200009010-00008
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Dysfunction in Men With Paraparesis in Lumbar Burst Fractures

Abstract: Neurologic recovery after lumbar fractures was improved. Regardless of neurologic recovery, most patients reported some disability, usually caused by pain and occasionally sexual dysfunction. Impairment of sexual function was present in four patients (9.3%). Although these patients may preserve psychiatric erection potential, they usually experienced sexual problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
3

Year Published

2002
2002
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 16 publications
1
4
0
3
Order By: Relevance
“…A previous study reported that ∼25% of SCI patients experience ED (12). As is customary for traditional cultures, discussion of sexuality is considered a taboo.…”
Section: Resultsmentioning
confidence: 99%
“…A previous study reported that ∼25% of SCI patients experience ED (12). As is customary for traditional cultures, discussion of sexuality is considered a taboo.…”
Section: Resultsmentioning
confidence: 99%
“…More than 60% of male patients injured by major pelvic trauma reported limitations in sexual function [16]. Regardless of neurological recovery after lumbar injuries, most patients reported some disability, usually caused by pain and occasionally SD [17]. ED is common in patients with extensive perineal trauma including distal urethral, testicular, and corporal injuries [18].…”
Section: Discussionmentioning
confidence: 99%
“…When a patient experienced pain in more than one site of his body, he was encouraged to provide a single, global estimate of pain intensity. (26)(27)(28)(29)(30), mild (17)(18)(19)(20)(21)(22)(23)(24)(25), moderate (11)(12)(13)(14)(15)(16), or severe (0-10) ED. The UKU is a wellvalidated questionnaire to assess side effects of psychotropic drugs in clinical studies and clinical practice.…”
Section: Methodsmentioning
confidence: 99%
“…Although the American Spinal Injury Association (ASIA) impairment scale helps to classify the extent of neurological injury, it does not provide any information regarding sexual function. 13 …”
Section: Effects Of Spinal Trauma On Sexual and Reproductive Functionmentioning
confidence: 99%